Identifying nutrient gaps and priority foods in Senegal - Domgho, Léa Magne; Collins, Julia; Ulimwengu, John M.; Badiane, Ousmane (AKADEMIYA2063, 2023)
Micronutrient deficiencies, sometimes referred to as “hidden hunger,” are often less visible than other forms of undernutrition but nevertheless constitute a major cause of severe health issues. In Senegal, micronutrient deficiencies are recognized as an important public health issue despite limited data on their extent and distribution. Senegal’s Strategic Multisectoral Nutrition Plan 2017–2021 (PSMN) (Government of Senegal, 2017) highlights micronutrient deficiencies as a major issue in Senegal’s nutrition landscape. The plan’s second major intervention axis focuses on alleviating micronutrient deficiencies, including for iron, folic acid, iodine, zinc, and Vitamin A. Two of the plan’s strategic goals focus on micronutrients, pledging to reduce the prevalence of anemia among vulnerable groups by 25 percent and to reduce the prevalence of iodine, zinc and Vitamin A deficiencies by 20 percent. Meeting these goals requires detailed evidence on the distribution of micronutrient deficiencies as well as exploration of different intervention avenues. This brief presents initial results of a study undertaken to estimate micronutrient adequacy among Senegalese households at a geographically disaggregated level. The work is part of a larger analysis carried out through the Nutrient Smart Processing and Trade (NSPT) project led by AKADEMIYA2063 in collaboration with Senegal’s Conseil National de Développement de la Nutrition with funding from the United States Agency of International Development (USAID) to identify priority avenues and interventions for addressing micronutrient deficiencies in Senegal. The NSPT analysis is based on the identification of three types of micronutrient adequacy levels and their distribution throughout the country: Nutrient Production Adequacy (NPA), Nutrient Market Adequacy (NMA), and Nutrient Household Adequacy (NHA). The three types of adequacy measures provide information on the production of micronutrients, the overall availability of micronutrients for consumption, and the adequacy of consumption at the household level